Redes de relacionamentos interorganizacionais no processo de internacionalização em casa : um estudo de caso no Recanto Park Hotel - Mario, Fábio Aurélio de (2017)
Internationalization has been widely discussed in several perspectives. In the same manner, the Theory of Interorganizational Relationship Networks has also gained space in academic discussions. One of the theoretical strand which still not much explored is the Internationalization at Home (IaH). Widespread, mostly in the Education segment, mainly to explain the internationalization of Higher Education Institutions, this process of internationalization proves to be as further an alternative approach for the internationalization of companies, especially service providers. The object of study was the Recanto Park Hotel, located in the tourist town of Foz do Iguaçu - PR. The theoretical constructs used have been elucidated, henceforth, on two aspects: (a) Internationalization at Home; (b) Interorganizational Relationship Networks. In the light of this proposition, the following research objective has been established: to understand how the interorganizational relationship network affects the process of Internationalization at Home of the Recanto Park Hotel. Supported by the qualitative research approach and the case study strategy, data have been collected through: (a) documents; (b) semi-structured interviews; (c) observation. The findings of the present research are divided into three moments. At first, the possibility of Internationalization at Home of soft services organizations is highlighted, in which the client composes his production process. Secondly, the role of interorganizational networks is relevant, above all, in relations with institutions and organizations, such as tourism agencies, guides and taxi drivers, thus composing part of the local tourist complex. At the third moment, three framework propositions are presented: (a) the process of internationalization of service organizations, in which ex ante and ex post elements are elucidated to internationalization; (b) a framework proposition for Internationalization at Home, which shows the existence of similar elements to the traditional internationalization process; (c) a framework of Internationalization at Home process, being extensively affected by ex post factors to internationalization.